PENGARUH FEAR OF MISSING OUT (FOMO), LITERASI KEUANGAN, DAN SELF CONTROL TERHADAP IMPULSIVE BUYING PADA MAHASISWA AKUNTANSI UNIVERSITAS WIJAYA KUSUMA SURABAYA - Miguel Nelson Soares Madeira; Surenggono Surenggono (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of Fear of Missing Out (FoMO), financial literacy, and self-control on impulsive buying among Accounting students at Wijaya Kusuma University Surabaya. This study employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 120 respondents selected using a purposive sampling technique. The data were analyzed using multiple linear regression with IBM SPSS Statistics version 26. The results of the partial test (t-test) indicate that Fear of Missing Out (FoMO) has a positive and significant effect on impulsive buying, with a significance value of 0.001. Financial literacy also has a positive and significant effect on impulsive buying, with a significance value of 0.000. Meanwhile, self-control has no significant effect on impulsive buying, with a significance value of 0.910. The simultaneous test (F-test) shows that FoMO, financial literacy, and self-control simultaneously have a significant effect on impulsive buying, with a significance value of 0.002. The findings of this study are expected to serve as an evaluation for students in managing their consumption behavior and as input for universities in strengthening financial literacy education and self-control development to minimize impulsive buying behavior.